Trade unions in Poland - Gardawski, Juliusz; Mrozowicki, Adam; Czarzasty, Jan (Brussels, 2012)
"This report on the trade union landscape in Poland forms part of a wide-ranging project, initiated and coordinated by the ETUI, which aims to map changes in unionisation and the varying organisational structures of unions in the ‘new member states’ of the European Union. The current report on the trade union movement in Poland is a real tour de force, especially given the vast number of union organisations entailed. The fruit of this tremendous effort on the part of the country experts is a report that is simultaneously comprehensive and extremely rich in detail. In mapping the full broad gamut of Polish trade unions, they compellingly expose how much the trade union movement in this country is handicapped by its excessively decentralised structures; its chronic fragmentation and rivalry at the company level and above; and the dramatic decline in membership levels, particularly in absolute terms."